2019
DOI: 10.1302/0301-620x.101b8.bjj-2018-1566.r1
|View full text |Cite
|
Sign up to set email alerts
|

Developing a standardized approach to virtual clinic follow-up of hip and knee arthroplasty

Abstract: Aims This study aimed to develop a virtual clinic for the purpose of reducing face-to-face orthopaedic consultations. Patients and Methods Anonymized experts (hip and knee arthroplasty patients, surgeons, physiotherapists, radiologists, and arthroplasty practitioners) gave feedback via a Delphi Consensus Technique. This consisted of an iterative sequence of online surveys, during which virtual documents, made up of a patient-reported questionnaire, standardized radiology report, and decision-guiding algorithm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In a study performed by El Ashmawy et al., it was found that less than 10% of patients needed an in-person appointment after their total joint arthroplasty [ 8 ]. In recent years, a standardized approach has been developed by numerous specialists involved in total joint arthroplasty patient care, which allows for the safe implementation of virtual arthroplasty clinics across the United Kingdom [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed by El Ashmawy et al., it was found that less than 10% of patients needed an in-person appointment after their total joint arthroplasty [ 8 ]. In recent years, a standardized approach has been developed by numerous specialists involved in total joint arthroplasty patient care, which allows for the safe implementation of virtual arthroplasty clinics across the United Kingdom [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Virtual clinic models have previously been developed and evaluated for hip and knee replacement follow-up, and are already established in some centres. 52,171 Each major regional centre should identify a radiography facility with the appropriate expertise to offer this service. This may be run by the radiology department, the orthopaedic department or a combined multidisciplinary team.…”
Section: Evidence-based Follow-up Recommendationsmentioning
confidence: 99%
“…Evidence-based standardised radiology reporting (e.g. reporting methods previously developed by members of the UK SAFE team 171 ) should be considered.…”
Section: Evidence-based Follow-up Recommendationsmentioning
confidence: 99%
“…In 2014, Sharareh and Schwarzkopf compared on-site postoperative follow-up visits with remote consultations and concluded that patients who underwent telemedicine follow-up rated their postoperative satisfaction higher [42]. More recently in 2019, Preston et al [37] provided a standardized approach and assessment of virtual follow-up of hip and knee arthroplasty patients. Their approach and methods of documentation were well accepted by orthopedic experts, radiologists, and patients.…”
Section: Performance Of Telemedicine Examinationmentioning
confidence: 99%